Anatomical parameters for musculoskeletal modeling of the hand and wrist. Issue 1 (1st January 2016) - Mirakhorlo, Mojtaba; Visser, Judith M. A.; Goislard de Monsabert, B. A. A. X.; van der Helm, F. C. T.; Maas, H.; Veeger, H. E. J.
Abstract: A musculoskeletal model of the hand and wrist can provide valuable biomechanical and neurophysiological insights, relevant for clinicians and ergonomists. Currently, no consistent data-set exists comprising the full anatomy of these upper extremity parts. The aim of this study was to collect a complete anatomical data-set of the hand and wrist, including the intrinsic and extrinsic muscles. One right lower arm, taken from a fresh frozen female specimen, was studied. Geometrical data for muscles and joints were digitized using a 3D optical tracking system. For each muscle, optimal fiber length and physiological cross-sectional area were assessed based on muscle belly mass, fiber length, and sarcomere length. A brief description of model, in which these data were imported as input, is also provided. Anatomical data including muscle morphology and joint axes (48 muscles and 24 joints) and mechanical representations of the hand are presented. After incorporating anatomical data in the presented model, a good consistency was found between outcomes of the model and the previous experimental studies.